VLF Emissions observed at the low latitude Indian station Varanasi - Patel, R.P.; Singh, A.K.; Singh, S.; Singh, Rajesh; Singh, K.; Singh, R.P. (My University, 2008)
VLF emissions such as hiss, chorus, pulsing hiss, triggered emissions observed at Varanasi (geom. lat. = 14° 55′ N, long. = 153° 55′ E) are reported. An attempt has been made to explain the dynamic spectra in terms of the generation mechanism and propagation through the inhomogeneous magnetoplasma. It is noted that the reported events have propagated along different L-values in the magnetosphere, although they have been recorded at the same station. The ULF waves propagating along geomagnetic field lines modulate the growth rate of VLF waves, which results in the pulsation of VLF hiss intensity. The pulsating growth rate has been computed.
Keywords: VLF Emissions; Whistler-Mode waves; Magnetosphere; Wave propagation; Low latitude; Varanasi